The Intersection of Science and Drama: Unveiling the Transformative Power of Dramatic Plays (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Dramatic plays have long captivated audiences with their vivid storytelling and emotional depth, but their potential as a powerful tool for scientific exploration and communication remains largely unexplored. This article delves into the multifaceted realm of dramatic plays, examining their ability to convey complex scientific concepts, engage diverse audiences, and stimulate critical thinking. By examining the fusion of science and drama, we aim to shed light on the transformative power of this unique art form, both as an educational tool and as a means to foster societal engagement with scientific knowledge.